Macedonia’s Preparations for Civilian Contribution to Peace Operations: the Next Big Thing After the Withdrawal From Afghanistan - Bogdanovski, Andreja (Journal of Regional Security, 2018)
Macedonia is lacking a strategy for civilian contribution to peace operations. There have been initiatives and sporadic attempts to address the issue but these were never intertwined into a coherent policy. Civilian participation in peace operations remains on the radar of Macedonia’s authorities and would largely benefit from external involvement in the form of provision of guidance both at strategic and operational levels. In times of austerity, blockade of EU and NATO processes and withdrawal from Afghanistan, putting an emphasis of civilian contributions to peace operations may be viewed as a natural continuation of Macedonia’s input to international peace and security. This paper aims to assess the developments related to Macedonia’s contribution to peace operations through civilian means by mapping its potential capacities and areas of expertise. It therefore outlines and recommends the development of civilian components for peace operations and post-conflict societies growing out of the experience that Macedonia has had in policing, crisis management and media training.